Procedure in developing neural network model - Mat Yamin, Fadhilah; Wan Ishak, Wan Hussain; Othman, Siti Norezam (2006)
Neural Networks are now widely used in many application domains such as business, engineering, manufacturing, construction and etc.Neural Networks can be used for forecasting and planning, clustering and pattern recognition. However, when developing Neural Networks model, there are some issues that should be considered. This study explores the issues and experiment with secondary data. The final output of the study is a step-bystep procedure to develop a Neural Networks model. This step-by-step procedure can be used to develop other Neural Networks for any domain.